2015
DOI: 10.3390/ma8052376
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of CdS Quantum Dots onto Hierarchical TiO2 Structure for Quantum Dots Sensitized Solar Cell Applications

Abstract: Quantum dot (QD) sensitized solar cells based on Hierarchical TiO2 structure (HTS) consisting of spherical nano-urchins on transparent conductive fluorine doped tin oxide glass substrate is fabricated. The hierarchical TiO2 structure consisting of spherical nano-urchins on transparent conductive fluorine doped tin oxide glass substrate synthesized by hydrothermal route. The CdS quantum dots were grown by the successive ionic layer adsorption and reaction deposition method. The quantum dot sensitized solar cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The hydrothermal reaction was performed in an oven at 180 °C for 12 h. Post reaction, the oven was cooled down normally. The solid particles were washed with ethanol and deionized water several times and dried overnight at 70 °C, followed by calcination at 450 °C for 60 min. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrothermal reaction was performed in an oven at 180 °C for 12 h. Post reaction, the oven was cooled down normally. The solid particles were washed with ethanol and deionized water several times and dried overnight at 70 °C, followed by calcination at 450 °C for 60 min. , …”
Section: Methodsmentioning
confidence: 99%
“…The solid particles were washed with ethanol and deionized water several times and dried overnight at 70 °C, followed by calcination at 450 °C for 60 min. 20,21 Synthesis of CdTe QDs. Synthesis of CdTe QDs was carried out under the aqueous phase by utilizing capping agents.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To attain improved light harvesting efficiency across a wide range of wavelengths, including the visible and near-infrared regions, quantum dots-based surface-emitting solar cells (QDSSCs) make use of the distinctive characteristics of colloidal quantum dots (QDs) (Ali et al, 2015).…”
Section: Enhanced Light Harvesting and Efficiencymentioning
confidence: 99%
“…The band gap of bulk CdS is ~2.42 eV from the literature [9]. The bandgap of FTO/TiO2/CdS-8 is higher than bulk, so it's indicated that CdS nanocrystals are obey the quantum confinement effect [22]. These electrons passed through the counterpart and then, enter the electrolyte and the process is repeated.…”
Section: Optical Studiesmentioning
confidence: 99%